From Stress to Strength: Investigating Mental Health in Humanitarian Aid and High-Risk Occupations - Martinmäki, Saara Elina (Utrecht University, 2024)
We investigated iHAWs’ mental health before, right after, and two months after their field assignments. While most workers maintained stable mental health, some experienced worsening symptoms over time, while others began their assignment with elevated levels of distress. Our findings indicate that factors such as a strong sense of coherence (SOC)—the ability to make sense of life’s challenges—act as protective factors. At the same time, longer assignments and being female were linked to a greater risk of worsening symptoms in common mental health conditions. Additionally, we examined various stressor types faced by iHAWs. Organisational stressors — such as high workload, unclear communications, or team conflicts — and general harassment were found to have a stronger link with mental health and work-related well-being than exposure to potentially traumatic events. Sexual harassment was also a significant contributor to poor mental health outcomes among female iHAWs. We found that when aid workers are exposed to multiple types of stressors, these stressors tend to have an additive effect, with each additional stressor further burdening their mental health. Finally, we studied the treatment of work-related trauma in a separate high-risk group: police officers. We found that an intensified trauma-focused treatment was effective for many treatment-resistant police officers with post-traumatic stress disorder (PTSD), though involvement in compensation procedures was associated with poorer treatment outcomes. Our research offers practical and policy-oriented recommendations for humanitarian organisations to enhance and protect the mental health of their staff.
Keywords: humanitarian aid; high-risk occupation; occupational stress; work stress; harassment; traumatic stress; police; sense of coherence